Identification of genetic mutations associated with autism in GABRB3 gene in Iraqi autistic patients - Yassin, Alya Hamza; Al-Kazaz, Abdul Kareem A.; Muhsin , Haider Abdul (Iraqi Journal of Science, 2022)
This study was aimed to detect and identify genetic mutations in γ-aminobutyric acid receptor β3 subunit encoding gene (GABRB3) and its association with autism spectrum disorders. Forty autistic patients and 25 non-autistic as control group (5 unaffected sibling and 20 unrelated) with age range from 3 – 10 years were included in this study. Chromosomal DNA was extracted from blood samples followed by polymerase chain reaction (PCR) amplification of two targeted regions which include: (exon2-intron2-exon3) region and (exon 6) region of GABRB3 for subsequent DNA sequencing. Identical bands related to the targeted regions were present in all samples. A sample of PCR products of patients and controls were sequenced. Sequencing results revealed the presence of four different single nucleotide polymorphism (SNPs) in four autistic patients (one SNP in exon2, two SNPs in intron 1 and one SNP in the beginning of intron 3) while four different autistic samples and three from control group had no mutations along this region. Exon 6 showed 100 % sequence identity in all samples (seven autistic and three from control group). The translation of nucleotides sequences into amino acid sequence revealed that the SNP in exon 2 caused a change of amino acid in the polypeptide sequence by changing the codon (AGA) which codes for arginine to (AAA) which codes for lysine. The online software tool, RaptorX was used for the prediction of the three dimensional structure of the polypeptides in which exon 2 carrying one SNP (30 a.a.) showed that 5 (16%) positions predicted as disordered, while the structure prediction of polypeptide translated from exon 3 was not obtained due to its small length (22 a.a.). Structure prediction of polypeptide of exon 6 (46 a.a.) showed that (0%) positions predicted as disordered, considering its lack of mutations. These results suggest the association of the detected SNPs with autism, especially the SNP located in exon 2 considering that it changed the polypeptide three dimensional structure, thus it could possibly alter its function. All SNPs are reported for the first time in this study except the one in intron 3 (rs755863611) which was previously reported.